Sentiment Analysis On The Conversation Pattern Of The @QUWEENJOJO Account's Apology Regarding Gofar Allegations Of Harassment On Twitter - Ludi Azhari Lesmana; Resman Muharul Tambunan; Imsar Gunawan; Safira Hasna (LONTAR: Jurnal Ilmu Komunikasi, 2024)
Social media has become a fundamental necessity for humans, facilitating social interaction and communication which are essential needs as social beings. In the era of social media, information about scandals or controversial actions can spread rapidly and widely. One notable case is Gofar Hilman, where public perception turned negative due to allegations of sexual harassment posted by the @Quweenjojo account. This research explores the sentiments and communication patterns arising from the public apology discussion by @Quweenjojo on Twitter regarding the allegations against Gofar Hilman. The tweets generated diverse responses from the audience, as the accusations of sexual harassment against Gofar Hilman by @Quweenjojo were deemed delusional and false. This study applies communication pattern theory and narrative analysis methods. The findings from the communication pattern theory analysis reveal a circular communication pattern formed during interactions, reflecting equal distribution in communication and decision-making processes. The research identifies predominantly negative sentiments resulting from this interaction. It suggests that public apologies on social media may not always yield positive outcomes for the apologizer and can instead worsen their reputation. The apology by @Quweenjojo could be viewed as an attempt to restore Gofar Hilman's reputation.